Optimization of PPA Unit Performance to Realize Professional Implementation of Diversion in Jepara Police - Budi, Ramadhama Setiawan (Advances in Police Science Research Journal, 2024)
Children are the next generation of the nation. The existence of children who conflict with the law must be sought for diversion with the terms and conditions in Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. The Criminal Investigation Unit, especially the PPA unit as the primary executor in the application of diversion in the Jepara Police area, plays a significant role in disclosing and resolving juvenile crime cases so that the situation and conditions of society become conducive according to what the community expects. The author's goal in conducting research is to identify the performance of the Criminal Investigation Unit, which is translated from the problem of investigator competence and management carried out by investigators to realize the implementation of professional diversion. The research was carried out using qualitative methods to obtain accurate data obtained through interviews, observation, and document studies, using primary and secondary data sources. Then the stages of data analysis used by the author are data reduction, data presentation, and conclusion. The study results show that in practice, the Jepara Polres PPA Investigators are influenced by two (2) internal and external factors. The internal factor that most affect the application of diversion in criminal investigations is the competence of investigators who do not yet have the knowledge, skills, and attitudes that are by the rules so that in practice, there are still mistakes that occur, while the external factors that influence are the absence of a Correctional Center in the Jepara district area. And also the lack of communication between agencies regarding the implementation of diversion. The conclusion is that the competence of PPA investigators is still not optimal in carrying out diversion through the criminal investigation process. There is still no visible effort by the community due to the many factors and obstacles that occur, so it is necessary to improve the quality of investigators through training and development education and carrying out the management stages, namely planning, organizing, implementing, and supervising as an effort to implement diversion.